Exploring the relationship between cognitive abilities and motor performance in athletes with intellectual disabilities - Luca Cavaggioni; Luca Cavaggioni; Damiano Formenti; Linda Casalini; Francesco Granito; Chiara Magro; Andrea Manente; Simona Canton; Nicola Lovecchio; Paolo Castiglioni; Paolo Castiglioni; Giampiero Merati; et al. (Frontiers in Sports and Active Living)
IntroductionBasketball practice for athletes with intellectual disabilities (ID) is an ancient activity that stimulates cognitive and motor performance domains. This study aims to verify the association between cognitive performance and motor abilities in basketball athletes with ID.MethodsA total of 23 participants with ID were screened on cognition (clinical reaction time and Bells test 30 s and 90 s), motor performance [handgrip strength test (HST), countermovement jump (CMJ), static balance], and anthropometry [body mass index (BMI) and skinfolds] in a cross-sectional design.ResultsA strong negative relationship was observed between clinical reaction time with HST and CMJ variables. A strong positive association was also found between Bells test 30 s with anthropometric variables (BMI) and power-related CMJ outcomes. Linear regression models revealed that the CMJ concentric mean force explained 34.3% of the variance of performance time during the clinical reaction time, and the HST combined with BMI explained 53% of the variance of cognitive ability during the Bells test 30 s.ConclusionsThese results suggest a positive correlation between cognitive and motor performance in basketball players with ID. These findings encourage further exploration of how sports interventions could ameliorate physical and cognitive health in individuals with ID.